O espaço jurídico das religiões: o debate sobre secularização visto pelo direito - Aquino, Theófilo Miguel de (2018)
The research draws on part of the debate about secularization to show how its authors do not use the legal practice in their diagnosis and how their conclusions are hampered by this obliviousness. It argues three major points against those authors. First, it will show that there is a legal reason why religions might have public influence nowadays. Second, it puts evidence to how the law also constitutes different forms of experimenting faith and different relations between religion and social life. Third, it sheds light on how the legal practice constitutes and regulates social conflicts in a unique way, without which those conflicts would become incomprehensible. These points allow for the occurrence of secularization in a specific sense, that is, the independence of law from a religious institutional environment. The dissertation thus goes back to the debate on secularization to show how each specific author needs to have its conclusions limited by the findings of the research. It is not the purpose to argue that they use the concept of secularization in a wrong way, but to show that their diagnosis do not have neither the reach nor the strength they intend to, for they do not analyze the conception of secularization that has to do with law. For some authors the research will impose significant limits; as for others, it will be able to complement their arguments by including new facts brought by the internal legal point of view.